Text Complexity in Reading Texts of Indonesian Senior High School English Textbooks Using Coh- Metrix 3.0 - Muhammad Zahrudhin Verdiansyah; Sahiruddin Sahiruddin; Putu Dian Danayanti Degeng (Unipdu Jombang, 2020)
AbstractThis study examined text complexity, mainly related to lexical/sematic and syntactical complexity. Two English textbooks of grade 10 and 12 of Indonesian senior high schools are assessed. Four reading texts in each book respectively selected based on text genre and word length. Coh-Metrix 3.0 was utilised. Descriptive statistics were presented, and Independent T-test was conducted to perceive differences on texts in the two textbooks. Finally, it was found that between grade 10 and grade 12, the complexity on both lexical and syntactical aspects showed no difference, but texts in grade 10 tend to produce significantly more consistent of the syntactic constructions than grade 12. It is suggested that texts in grade 12 should be revised to meet reading texts based on their levels relating to character of sophistication of language complexity.Keywords: Lexical Complexity, Reading, Syntactical Complexity AbstrakPenelitian ini mengkaji kompleksitas pada teks, terutama yang berhubungan pada kompleksitas leksikal/semantik dan sintaktik. Dua buku Bahasa Inggris Sekolah Menengah Keatas kelas 10 dan 12 yang dinilai. 4 teks bacaan masing-masing pada setiap buku dipilih berdasarkan genre teks dan panjang teks. Coh-Metrix 3.0 yang dipakai. Deskriptif statistik dipersembahkan dan Independent T-test dilakukan untuk melihat perbedaan pada teks di dua buku tersebut. Akhirnya, ditemukan bahwasanya diantara kedua buku (kelas 10 dan 12), kompleksitas pada aspek leksikal maupun sintaksis menunjukkan tidak ada perbedaan, tetapi teks di kelas 10 secara signifikan cenderung lebih konsisten pada konstruksi sintaksisnya daripada di kelas 12. Hal ini disarankan bahwa teks pada kelas 12 sebaiknya direvisi agar sesuai dengan level terkait dengan karakter kekompleksitasan kebahasaanya.Keywords: Bacaan, Kompleksitas Leksikal, Kompleksitas Sintaktik